Investigating Students’ Metacognitive Awareness Inventory in Listening Comprehension - Sinaga, Juwita Boneka; Eriyanti, Ribut Wahyu; Asih, Ria Arista (Lectura : Jurnal Pendidikan, 2024)
Understanding listening skills is vital in language learning, yet many students struggle with it, partly due to low metacognitive awareness. This research emphasizes the importance of metacognitive awareness in language learning, specifically in listening comprehension. Students often face challenges due to low metacognitive awareness, affecting their ability to plan, monitor, and evaluate listening strategies. The urgency of this study lies in enhancing listening skills through improved metacognitive training, which can aid in effective listening comprehension and overall academic performance. By identifying these areas of need, educators can better tailor teaching methods and curricula to foster more active and reflective listening in students, ultimately benefiting their language learning journey. This study aims to investigate the relationship between metacognitive awareness and listening comprehension among high school students. Conducted in two classes with a total of 39 students, the research employed a quantitative design using the “Metacognitive Awareness Inventory for Listening (MAIL)” and a “Listening Comprehension Test.” Data were analyzed using descriptive statistics and independent samples t-tests to compare scores between the two classes. Results indicated no significant differences in metacognitive awareness (p = 0.638) and listening comprehension (p = 0.431) between the two groups. These findings suggest that other contextual factors, beyond metacognitive awareness, may influence listening comprehension. Further research is recommended to explore these additional factors and their impact on students’ listening skills and metacognitive strategies in educational contexts.